2015
DOI: 10.1590/0103-6440201300225
|View full text |Cite
|
Sign up to set email alerts
|

Demineralization and Hydrogen Peroxide Penetration in Teeth with Incipient Lesions

Abstract: The aim of this study was to evaluate the demineralization and hydrogen peroxide (HP) penetration in teeth with incipient lesions submitted to bleaching treatment. For analysis of HP penetration, sound and demineralized enamel/dentin discs were placed in artificial pulp chambers containing acetate buffer solution. After bleaching treatment, this solution was subjected for analysis of optical density by spectrophotometry and the disc surfaces were analyzed with scanning electron microscopy (SEM) and polarized l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 24 publications
1
20
1
Order By: Relevance
“…In the present study, the concentration of hydrogen peroxide found in the pulp chamber for 35% HP group was higher than other published studies [18,22,23]. Amounts of HP ranging from 1.22 to 6.22 µg was observed in the pulp chamber of teeth bleached with 35% hydrogen peroxide in other studies [18,22,23], while in the present study an average of 28.5 µg was detected for 35% HP group. These differences may be attributed to variations in the experimental design such as the type of dental substrate used (human or bovine), composition of the gels, experimental protocol, hydrogen peroxide delivery method and differences of cavity preparation.…”
Section: Discussioncontrasting
confidence: 77%
“…In the present study, the concentration of hydrogen peroxide found in the pulp chamber for 35% HP group was higher than other published studies [18,22,23]. Amounts of HP ranging from 1.22 to 6.22 µg was observed in the pulp chamber of teeth bleached with 35% hydrogen peroxide in other studies [18,22,23], while in the present study an average of 28.5 µg was detected for 35% HP group. These differences may be attributed to variations in the experimental design such as the type of dental substrate used (human or bovine), composition of the gels, experimental protocol, hydrogen peroxide delivery method and differences of cavity preparation.…”
Section: Discussioncontrasting
confidence: 77%
“…(1) studies that compared the effects of the bleaching gel on the pulp tissue with and without the use of light or heat; (2) in vivo and in vitro studies; and (3) studies published in English. The exclusion criteria were (1) studies comparing only the effects of bleaching gel without light or only bleaching gel with light and (2) duplicated studies.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Studies have shown that hydrogen peroxide (HP) in bleaching gels can cause morphological alterations in the dental surface, such as the reduction of the enamel hardness and increased roughness [1,2], in addition to histochemical alterations [3]. Furthermore, bleaching agents release reactive oxygen species (ROS) that reach the pulp tissue and cause cell damage [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In-office bleaching is a popular dental aesthetic treatment option because of its high success rate (1). Several methods and approaches have been described in the literature for bleaching vital teeth, such as different bleaching agents, concentrations, time of application and product presentation (2).…”
Section: Introductionmentioning
confidence: 99%